Pembinaan di Bidang Pemasaran dan Permodalan kepada Industri Pengolahan Kulit Ikan di Kabupaten Karawang - Hakim, Heikal Muhammad Zakaria; Nopiana, Medi; Latuconsina, Husain (Politeknik Negeri Samarinda, 2024)
The production process in the fish processing industry indeed produces waste, including fish skin. The fish skin waste is then processed by the fish skin processing industry, one of which is in Tegalsari Village, Cilamaya Wetan Subdistrict, Karawang Regency, so the waste can be helpful and has more added value. In practice, this industry experiences several problems in its development, especially marketing and capital problems. Universitas Singaperbangsa Karawang and other universities took the initiative to hold community service activities, such as coaching for the industry actors. The coaching activity aims to obtain solutions for the fish skin processing industry in this village to the two problems. The coaching method is carried out through counseling for the management of the Berkah Mandiri Women's Cooperative as players in the fish skin processing industry in the village. It requires the involvement of all stakeholders and synergy between them so that the industry's problems can be resolved effectively and thoroughly.